Fabrication and UV‐sensing properties of one‐dimensional β‐Ga2O3 nanomaterials. Issue 9 (14th June 2013) - Feng, Haifeng; Hao, Weichang; Zhao, Changzheng; Xin, Xiandong; Cheng, Jinyang; Cui, Yimin; Chen, Yan; Wang, Wenjun
<x xml:space="preserve">Abstract</x> β‐Ga2O3 nanowires and nanobelts with a length range of tens of micrometers to a few millimeters were successfully fabricated by a simple in situ chemical vapor deposition (CVD) method under normal pressure without any catalysts. The morphology and microstructure of the samples were studied by SEM, XRD, and EDS. The results indicated that the morphology of Ga2O3 depends on the effective heating time. Ga2O3 nanostructures were mainly collected at the gallium source position instead of in the downstream area. So, we propose that the growth process can be explained by a vapor–solid (VS) model. The ultraviolet (UV) sensing properties of a single nanowire were tested. From the nonlinear I–V curves, we find that a single nanowire behaves as a rectifier and has asymmetric characteristics. The photoresponse characterization presents that response time and recovery time were about 0.32 and 0.08 s, respectively. Our result indicated that a single β‐Ga2O3 nanowire possesses excellent UV sensing properties and it should be a good candidate for UV‐sensor development.